Differences in Mobile Banking trust Amongst Generation Y Consumers of the Major South African Retail Banks: Array - Van Deventer, Marko (Acta Universitatis Danubius. Œconomica, 2020)
Mobile banking is beneficial in terms of saving time and money as well as convenience and efficiency. However, given its cybernetic nature and risks associated with its use, trust issues are created. Therefore, it is important that retail banks ensure that their mobile banking channel is trustworthy. As such, the purpose of this study was to establish whether Generation Y consumers of the major South African retail banks differ in their mobile banking trust. Following a descriptive and single cross-sectional research design, self-administered survey questionnaires were completed by a convenience sample of 334 Generation Y consumers. The data was analysed using descriptive statistics, reliability and validity measures, Pearson’s product-moment correlation analysis, collinearity diagnostics and one-way analysis of variance (ANOVA). The findings indicate that there are differences between Generation Y consumers of the major South African retail banks and perceived trust in mobile banking, the integrity of the mobile bank, mobile banking structural assurances as well as the information quality of mobile banking. Understanding the differences in mobile banking trust and its related dimensions amongst Generation Y consumers of the major South African retail banks, retail banks can strategise to allay these consumers’ trust concerns, foster greater trust in their mobile channels as well as gain a competitive advantage and maintain consumer loyalty amongst this cohort of consumers.